Ethical issues with testing and treatment for Krabbe disease. (15th May 2019) - Ehmann, Paul; Lantos, John D
Abstract : Early‐infantile Krabbe disease (EIKD) is an autosomal recessive, progressive, neurodegenerative disorder that usually leads to death in infancy. A study published in 2005 indicated that hematopoietic stem‐cell transplantation (HSCT) was effective in the treatment for EIKD when used before the onset of symptoms. This finding suggested that newborn screening for EIKD, which would allow earlier diagnosis, might lead to earlier treatment and better outcomes. In 2006, New York was the first state to implement newborn screening for Krabbe disease; however, the results were not as good as proponents had hoped. In this paper, we present the history of efforts to diagnose and treat EIKD. Based on our findings, we question the efficacy of newborn screening for Krabbe disease. We present two arguments. First, testing itself is too imprecise. Even with the most rigorous testing standards, such as those used in New York, many of the children who are identified as being 'at risk' for EIKD remain asymptomatic. It is unclear if they will remain asymptomatic forever and, thus, whether the tests should be considered 'false positives', or whether they will eventually develop the disease. Second, we question the efficacy of early HSCT. We recommend placing a moratorium on mandatory newborn screening for EIKD. What this paper adds: Current tests to identify which children are likely to develop Krabbe diseased are inadequate. Many children identified as being 'at risk' for early infantile Krabbe disease remain asymptomatic. Psychosine appears to be more specific than low galactosylceramidase levels for diagnosing early infantile Krabbe disease. What this paper adds: Current tests to identify which children are likely to develop Krabbe diseased are inadequate. Many children identified as being 'at risk' for early infantile Krabbe disease remain asymptomatic. Psychosine appears to be more specific than low galactosylceramidase levels for diagnosing early infantile Krabbe disease. This article is commented on by Orsini on page 1354 of this issue.